ZAKAT FITRAH DENGAN UANG MENURUT IMAM HANAFI DAN IMAM MALIKI - Iin Pitriani; Siti Zailia; Legawan Isa (Muqaranah, 2021)
Abstract Zakat fitrah is issuing a special portion of property that has reached the nishab (quantity limit that requires zakat) to people who are most entitled to receive it or called mustahiq. The obligation to pay zakat fitrah is also legal in several verses in the Qur'an. The form of giving zakat fitrah has also been explained in several hadiths of the Prophet Muhammad. Efforts to pay zakat in Islamic law show that Islam is very concerned about social problems, especially the fate of those who are weak. So that close the relationship of love between fellow human beings in realizing Islamic brotherhood. In the Indonesian community, most of whom adhere to the Hanafi school of thought, but there are also some people who follow the guidelines of the Maliki school of thought, where from the two schools of thought there are differences of opinion about most of them allowing zakat fitrah with money, but there are also those who argue that paying zakat fltrah is not allowed with money. but with goods (basic materials). Based onthe explanation ofthe background of theproblem, the researcher determines the formulation of the problem, namely how are the similarities and differences between zakat fltrah and moneyaccording to Imam Hanafi andImam Maliki. This study uses the library research method, which means an activity to search, record, formulate to analyze to compile data about differences of opinion from Imam Hanafi and Imam Maliki regarding the payment of zakat fitrah with money. The dta obtained from the resultsof this library rsearch ar then processed systematically. The results in the study state that Imam Hanafi and Imam Malik both require zakat fitrah on people who have excess food the next day. However, in this case Imam Hanafi distinguishes between fard and obligatory. Fardhu is everything that is determined based on the qath'i argument, obligatory based on the zanni argument. Meanwhile, Imam Maliki does not distinguish between fard and obligatory. While the difference is that Imam Hanafi is allowed to pay zakat fitrah with money while Imam Maliki does not allow zakat firah with money, he must use local staple foods Keywords: Zakat, Money, Hanafi, Maliki